Multiple Roles of Brd4 in the Infectious Cycle of Human Papillomaviruses - McBride, Alison A.; Warburton, Alix; Khurana, Simran (Frontiers in Molecular Biosciences, 2021)
Human Papillomaviruses (HPV) reproduce in stratified epithelia by establishing a reservoir of low- level infection in the dividing basal cells and restricting the production of viral particles to terminally differentiated cells. These small DNA viruses hijack pivotal cellular processes and pathways to support the persistent infectious cycle. One cellular factor that is key to multiple stages of viral replication and transcription is the BET (bromodomain and extra-terminal domain) protein, Brd4 (Bromodomain containing protein 4). Here we provide an overview of the multiple interactions of Brd4 that occur throughout the HPV infectious cycle.